Comparative Transcriptomic Analyses Identify Candidate Genes for Convergent Reproductive Shifts in a Bimodal Viviparous Amphibian - Kevin P. Mulder; André Lourenço; Ivan Gomez‐Mestre; Miguel Carneiro; David Buckley; Iñigo Martínez‐Solano; Robert C. Fleischer; Rayna C. Bell; Guillermo Velo‐Antón (Molecular Ecology, 2026)
Shifts in reproductive mode represent key evolutionary innovations that shape species' life histories and evolutionary trajectories. Species showing bimodal reproductive strategies with multiple independent origins offer a rare opportunity to gain insights into the adaptive processes and mechanisms underlying convergent traits. The fire salamander, Salamandra salamandra , is the only amphibian exhibiting intraspecific variation in reproductive mode across multiple independent reproductive shifts, enabling investigation of the transition between larviparity (females give birth to aquatic larvae) and pueriparity (females give birth to fully developed terrestrial juveniles) within a single species and across different timescales. Pueriparity is an adaptive innovation that skips the aquatic larval stage, allowing individuals to exploit habitats with no available water bodies. The fire salamander is larviparous across most of its range, but pueriparity has evolved independently at least three times: once in the early Pleistocene within S. s. bernardezi in the mountains of northern Spain, and more recently on two land‐bridge islands (NW Spain) inhabited by S. s. gallaica . To identify candidate genes associated with these distinct reproductive modes, we compared gene expression profiles of the uterus and oviduct of pregnant females across two independent evolutionary transitions using RNA‐sequencing. We detected shared changes in maternal gene expression among pueriparous S. s. bernardezi and S. s. gallaica relative to their larviparous counterparts, in addition to differences unique to each independent evolutionary transition. Functional enrichment analyses indicated that differentially expressed genes were associated with reproductive timing, angiogenesis, and maternal signalling, consistent with the phenotypic differences observed in the uterine environment and embryonic development between the two reproductive modes. This study represents an important first step towards understanding the genomic basis of the evolution of pueriparity in a remarkable bimodal reproductive system, and provides transcriptomic resources and candidate genes for future research into the genomic architecture underlying this poorly understood adaptive trait.

Quaternary ammonium compounds (QACs), QAC resistance genes, and QAC-tolerant bacteria in livestock and human waste streams - Sophie Lennartz; Osas Elizabeth Aigbekaen; Alexandra Jahraus; Jan Siemens; Ines Mulder; Stefanie P. Glaeser (Journal of Hazardous Materials, 2026)

Differential Immune Responses Correlate With Chytridiomycosis Severity in Italian Crested Newts - Léa Fieschi‐Méric; Kevin P. Mulder; Eduardo Fernández Meléndez; Sarah Van Praet; Sofie De Bruyckere; Michael Fahrbach; Frank Pasmans; An Martel (Molecular Ecology, 2026)
In the midst of the current biodiversity crisis, amphibians are severely threatened by emerging diseases such as chytridiomycosis. Characterizing the mechanisms that underlie susceptibility to this disease is fundamental to improve amphibian conservation. Using a comprehensive multi‐omics approach, this study investigates the impact of an exposure to the chytrid fungus Batrachochytrium salamandrivorans ( Bsal ) on the gene expression of Italian crested newts ( Triturus carnifex ) and on the bacterial symbionts that constitute their skin microbiota. Exposure to Bsal affected multiple components of the newts' immunity, from limited structural changes in their microbiota and decreased expression of keratin‐encoding genes in the skin to the upregulation of genes involved in inflammation and adaptive immunity both at the site of infection (skin) and in their primary lymphoid organ (spleen). We found that chytridiomycosis severity was positively correlated with the downregulation of basal metabolism and with the upregulation of immune responses and of tissue restructuration. Together, our results suggest that in T. carnifex , Bsal susceptibility may be linked to a reallocation of energy resources from the maintenance of basal metabolism and tissue integrity towards elevated immunity and tissue restructuration.

Exposure to diesel exhaust particles accelerated neuronal cell death in xenoferroptosis-susceptible cells - Hong Yan; Leshan Zhang; Daan P. Bergsma; Phoeja S. Gadjdjoe; Alessandra Tosato; Mohammad S. Rahman; Kristel Mulder; Joelle van Trigt; Karim Rafie; Christina H.T.J. Mol-van der Veen; Remco H.S. Westerink; Flemming R. Cassee; et al. (Journal of Environmental Sciences, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

RIPPL, a Python-based InSAR stack and tropospheric delay software package - G. Mulder; F.J. van Leijen; P. Lopez-Dekker; R.F. Hanssen (Computers & Geosciences, 2026)

Whole-genome characterisation of Escherichia coli isolates from older women with urinary tract infection and asymptomatic bacteriuria - Marlies Mulder; Manu P. Bilsen; Martha T. van der Beek; Antoni P. A. Hendrickx; Angela de Haan; Merel M. C. Lambregts; Caroline Schneeberger-van der Linden (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Rapid mineralization of mineral-bound carboxyl-carbon of salicylic acid and phenylalanine - Alexander Konrad; Diana Hofmann; Jan Siemens; Friederike Lang; Ines Mulder; Kenton P. Stutz (Soil Biology and Biochemistry, 2026)

Divergent regulation of cellular cholesterol metabolism by seaweed-derived fucosterol and saringosterol - Na Zhan; Nikita Martens; Yanlin Li; Gardi Voortman; Frank Leijten; Silvia Friedrichs; Martien P. M. Caspers; Lars Verschuren; Tim Vanmierlo; Marieke Smit; Folkert Kuipers; Johan W. Jonker; et al. (Frontiers in Marine Science, 2025)
Marine sterols from brown seaweeds, particularly fucosterol and its oxidized derivative saringosterol, have shown therapeutic potential for Alzheimer’s disease (AD) and cardiovascular diseases. Here, we aimed to elucidate the cellular and in vivo mechanisms underlying their beneficial effects. In human HepG2 hepatocytes and CCF-STTG1 astrocytoma cells, we assessed liver x receptor (LXRα /LXRβ) activation, sterol uptake, and effects on cholesterol metabolism using luciferase reporter assays, GC–MS sterol profiling, and 13 C-acetate incorporation. In THP-1–derived macrophages, we evaluated sterol-induced cholesterol efflux using radiolabeled [ 3 H]-cholesterol assays and characterized anti-inflammatory responses by quantifying lipopolysaccharide (LPS) -induced cytokine production. Wild-type C57BL/6J mice were fed diets enriched with either fucosterol (0.2% w/w) or saringosterol (0.02% w/w) for 7 days, after which sterol profiles in serum, liver, and brain were quantified by GC–MS. Hippocampal transcriptional responses were assessed by RNA sequencing. Both fucosterol and saringosterol were internalized by HepG2 and CCF-STTG1 cells and activated LXRα/β, but elicited distinct metabolic effects: fucosterol increased cholesterol synthesis and intracellular desmosterol, whereas saringosterol reduced both; only saringosterol suppressed LPS-induced interleukin (IL)-6 and tumor necrosis factor (TNF)-α production in macrophages, while both enhanced cholesterol efflux. In vivo , fucosterol somewhat elevated hepatic desmosterol and decreased 5α-cholestanol and circulating oxysterols, whereas saringosterol also increased hepatic desmosterol and elevated 7α-hydroxycholesterol in liver and brain as well as serum 27-hydroxycholesterol. Transcriptome analysis revealed that fucosterol primarily modulated synaptic signaling and hormonal pathways linked to neuronal plasticity, while saringosterol affected protein quality control and neurodegenerative pathways. These data are the first on the direct comparison of the cellular and in vivo effects of fucosterol and saringosterol, revealing shared LXR activation but divergent impacts on hepatic, brain and systemic cholesterol metabolism and expression of genes involved in neural pathways, indicating complementary neuroprotective effects with therapeutic potential for AD and related disorders.

P05-01 Chronic dioxin exposure aggravates endothelial damage and left ventricular diastolic dysfunction only in male obese mice - G. Berge; R. Courcoux; M. Quétin; C. Dubois; F. Relaix; P. Mulder; M. Mericskay; M. Gervais (Toxicology Letters, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Microbial carbon use efficiency of mineral-associated organic matter is related to its desorbability - Alexander Konrad; Diana Hofmann; Jan Siemens; Kenton P. Stutz; Friederike Lang; Ines Mulder (Soil Biology and Biochemistry, 2025)

Downstream effects of the pandemic? Spatiotemporal trends of quaternary ammonium compounds in suspended particulate matter of German rivers - Sophie Lennartz; Jan Koschorreck; Bernd Göckener; Karlheinz Weinfurtner; Andrea Frohböse-Körner; Jan Siemens; Sanjana Balachandran; Stefanie P. Glaeser; Ines Mulder (Journal of Hazardous Materials, 2024)

Maternal serum PlGF associates with 3D power doppler ultrasound markers of utero-placental vascular development in the first trimester: the rotterdam periconception cohort - Eline S. de Vos; A. H. Jan Danser; Anton H. J. Koning; Sten P. Willemsen; Lotte E. van der Meeren; Eric. A. P. Steegers; Régine P. M. Steegers-Theunissen; Annemarie G. M. G. J. Mulders (Angiogenesis, 2024)
Objective (s) Circulating angiogenic factors are used for prediction of placenta-related complications, but their associations with first-trimester placental development is unknown. This study investigates associations between maternal angiogenic factors and utero-placental vascular volume (uPVV) and utero-placental vascular skeleton (uPVS) as novel imaging markers of volumetric and morphologic (branching) development of the first-trimester utero-placental vasculature. Methods In 185 ongoing pregnancies from the VIRTUAL Placenta study, a subcohort of the ongoing prospective Rotterdam Periconception cohort, three-dimensional power Doppler ultrasounds of the placenta were obtained at 7–9–11 weeks gestational age (GA). The uPVV was measured as a parameter of volumetric development and reported the vascular quantity in cm 3 . The uPVS was generated as a parameter of morphologic (branching) development and reported the number of end-, bifurcation- crossing- or vessel points and total vascular length. At 11 weeks GA, maternal serum biomarkers suggested to reflect placental (vascular) development were assessed: placental growth factor (PlGF), soluble fms-like tyrosine kinase-1 (sFlt-1) and soluble endoglin (sEng). sFlt-1/PlGF and sEng/PlGF ratios were calculated. Multivariable linear regression with adjustments was used to estimate associations between serum biomarkers and uPVV and uPVS trajectories. Results Serum PlGF was positively associated with uPVV and uPVS development (uPVV: β = 0.39, 95% CI = 0.15;0.64; bifurcation points: β = 4.64, 95% CI = 0.04;9.25; crossing points: β = 4.01, 95% CI = 0.65;7.37; total vascular length: β = 13.33, 95% CI = 3.09;23.58, all p-values Conclusion(s) Higher first-trimester maternal serum PlGF concentration is associated with increased first-trimester utero-placental vascular development as reflected by uPVV and uPVS. Clinical trial registration number Dutch Trial Register NTR6854.

Recommendations for the safe use of direct oral anticoagulants in patients with cirrhosis based on a systematic review of pharmacokinetic, pharmacodynamic and safety data - Maaike M. E. Diesveld; Daniëlle W. M. Jacobs- Pijnenburg; Rianne A. Weersink; Ina Barzel; Joost P. H. Drenth; Ton Lisman; Herold J. Metselaar; Margje H. Monster-Simons; Midas B. Mulder; Eline Okel; Katja Taxis; Sander D. Borgsteede (European Journal of Clinical Pharmacology, 2024)

An epigenome-wide association study of child appetitive traits and DNA methylation - Holly A. Harris; Chloe Friedman; Anne P. Starling; Dana Dabelea; Susan L. Johnson; Bernard F. Fuemmeler; Dereje Jima; Susan K. Murphy; Cathrine Hoyo; Pauline W. Jansen; Janine F. Felix; Rosa H. Mulder (Appetite, 2023)

Ectoparasite presence and brood size manipulation interact to accelerate telomere shortening in nestling jackdaws - Elisa P. Badás; Christina Bauch; Jelle J. Boonekamp; Ellis Mulder; Simon Verhulst (Molecular Ecology, 2023)
Early‐life conditions impact fitness, but whether the combined effect of extrinsic stressors is additive or synergistic is not well known. This is a major knowledge gap because exposure to multiple stressors is frequent. Telomere dynamics may be instrumental when testing how stressors interact because many factors affect telomere shortening, and telomere shortening predicts survival. We evaluated the effect of manipulated brood size and natural infestation by the carnid fly Carnus hemapterus on nestling growth and telomere shortening of wild jackdaws ( Corvus monedula ). Telomere length, measured in blood using TRF, shortened on average by 264 bp, and on average, Carnus infection induced more telomere shortening. Further analyses showed that in enlarged broods, nestlings' telomeres shortened more when parasitized, while in reduced broods there was no effect of infection on telomere shortening. We conclude that there is a synergistic effect of number of siblings and Carnus infection on telomere shortening rate: blood‐sucking parasites may negatively impact telomeres by increasing cell proliferation and/or physiological stress, and coping with infection may be less successful in enlarged broods with increased sibling competition. Larger nestlings had shorter telomeres independent of age, brood manipulation or infection. Growth was independent of infestation but in enlarged broods, nestlings were lighter at fledging. Our findings indicate that (i) evaluating consequences of early‐life environmental conditions in isolation may not yield a full picture due to synergistic effects, and (ii) effects of environmental conditions may be cryptic, for example, on telomeres, with fitness consequences expressed beyond the temporal framework of the study.

LP-16: Combining in vitro data and physiologically based kinetic modeling to predict liver toxicity of pyrrolizidine alkaloid rinderine in humans - S. Suparmi; S. Yuliyanti; P. Mulder; I. Rietjens (Toxicology Letters, 2023)

Occurrence and associated health risks of pyrrolizidine alkaloids in supplements marketed in Ghana for improved sexual performance - Felicia Akuamoa; Patrick P. J. Mulder; Toine F. H. Bovee; Ivonne M. C. M. Rietjens; Ron L. A. P. Hoogenboom (Food Additives & Contaminants Part B-Surveillance, 2023)

Beyond headcount statistics: Exploring the utility of energy poverty gap indices in policy design - T.M. Croon; J.S.C.M. Hoekstra; M.G. Elsinga; F. Dalla Longa; P. Mulder (Energy Policy, 2023)

Quaternary sedimentary processes on the Bahamas: From platform to abyss - K. Fauquembergue; E. Ducassou; T. Mulder; J.J.G. Reijmer; J. Borgomano; A. Recouvreur; V. Hanquiez; C. Betzler; M. Principaud; L. Chabaud; N. Fabregas; J. Giraudeau; et al. (Marine Geology, 2023)

High-resolution temporal wastewater treatment plant investigation to understand influent mass flux of per- and polyfluoroalkyl substances (PFAS) - Drew Szabo; Jaye Marchiandi; Subharthe Samandra; Julia M. Johnston; Raoul A. Mulder; Mark P. Green; Bradley O. Clarke (Journal of Hazardous Materials, 2023)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Speciation with gene flow in a narrow endemic West Virginia cave salamander (Gyrinophilus subterraneus) - Evan H. Campbell Grant; Kevin P. Mulder; Adrianne B. Brand; Douglas B. Chambers; Addison H. Wynn; Grace Capshaw; Matthew L. Niemiller; John G. Phillips; Jeremy F. Jacobs; Shawn R. Kuchta; Rayna C. Bell (Conservation Genetics, 2022)

Bioassay-directed analysis-based identification of relevant pyrrolizidine alkaloids - Jochem Louisse; Patrick P. J. Mulder; Arjen Gerssen; Geert Stoopen; Deborah Rijkers; Milou G. M. van de Schans; Ad A. C. M. Peijnenburg (Archives of Toxicology, 2022)
Pyrrolizidine alkaloids (PAs) are produced by various plant species and have been detected as contaminants in food and feed. Monitoring programmes should include PAs that are present in relevant matrices and that exhibit a high toxic potential. The aim of the present study was to use a bioassay-directed analysis approach to identify relevant PAs not yet included in monitoring programmes. To that end, extracts of Heliotropium europaeum and H. popovii were prepared and analysed with LC–MS/MS for the presence of 35 PAs included in monitoring programmes, as well as for genotoxic activity in the HepaRG/γH2AX assay. Europine, heliotrine and lasiocarpine were found to be the most abundant PAs. The extracts showed a higher γH2AX activity than related artificial mixtures of quantified known PAs, which might point to the presence of unknown toxic PAs. The H. europaeum extract was fractionated and γH2AX activities of individual fractions were determined. Fractions were further analysed applying LC–Orbitrap-MS analysis and Compound Discoverer software, identifying various candidate PAs responsible for the non-explained genotoxic activity. Altogether, the results obtained show that bioassay-directed analysis allows identification of candidate PAs that can be included in monitoring programmes.

Pigeon pea biochar addition in tropical Arenosol under maize increases gross nitrification rate without an effect on nitrous oxide emission - J. L. Munera-Echeverri; V. Martinsen; P. Dörsch; A. Obia; J. Mulder (Plant and Soil, 2022)

Speciation and secondary contact in a fossorial island endemic, the São Tomé caecilian - Kyle A. O’Connell; Ivan Prates; Lauren A. Scheinberg; Kevin P. Mulder; Rayna C. Bell (Molecular Ecology, 2021)
A period of isolation in allopatry typically precedes local adaptation and subsequent divergence among lineages. Alternatively, locally adapted phenotypes may arise and persist in the face of gene flow, resulting in strong correlations between ecologically‐relevant phenotypic variation and corresponding environmental gradients. Quantifying genetic, ecological, and phenotypic divergence in such lineages can provide insights into the abiotic and biotic mechanisms that structure populations and drive the accumulation of phenotypic and taxonomic diversity. Low‐vagility organisms whose distributions span ephemeral geographic barriers present the ideal evolutionary context within which to address these questions. Here, we combine genetic (mtDNA and genome‐wide SNPs) and phenotypic data to investigate the divergence history of caecilians (Amphibia: Gymnophiona) endemic to the oceanic island of São Tomé in the Gulf of Guinea archipelago. Consistent with a previous mtDNA study, we find two phenotypically and genetically distinct lineages that occur along a north‐to‐south axis with extensive admixture in the centre of the island. Demographic modelling supports divergence in allopatry (~300 kya) followed by secondary contact (~95 kya). Consequently, in contrast to a morphological study that interpreted latitudinal phenotypic variation in these caecilians as a cline within a single widespread species, our analyses suggest a history of allopatric lineage divergence and subsequent hybridization that may have blurred species boundaries. We propose that late Pleistocene volcanic activity favoured allopatric divergence between these lineages with local adaptation to climate maintaining a stable hybrid zone in the centre of São Tomé Island. Our study joins a growing number of systems demonstrating lineage divergence on volcanic islands with stark environmental transitions across small geographic distances.

Progression and Classification of Granular Osmiophilic Material (GOM) Deposits in Functionally Characterized Human NOTCH3 Transgenic Mice - Gido Gravesteijn; Leon P. Munting; Maurice Overzier; Aat A. Mulder; Ingrid Hegeman; Marc Derieppe; Abraham J. Koster; Sjoerd G. van Duinen; Onno C. Meijer; Annemieke Aartsma-Rus; Louise van der Weerd; Carolina R. Jost; et al. (Translational Stroke Research, 2020)
CADASIL is a NOTCH3 -associated cerebral small vessel disease. A pathological ultrastructural disease hallmark is the presence of NOTCH3-protein containing deposits called granular osmiophilic material (GOM), in small arteries. How these GOM deposits develop over time and what their role is in disease progression is largely unknown. Here, we studied the progression of GOM deposits in humanized transgenic NOTCH3 Arg182Cys mice, compared them to GOM deposits in patient material, and determined whether GOM deposits in mice are associated with a functional CADASIL phenotype. We found that GOM deposits are not static, but rather progress in ageing mice, both in terms of size and aspect. We devised a GOM classification system, reflecting size, morphology and electron density. Six-month-old mice showed mostly early stage GOM, whereas older mice and patient vessels showed predominantly advanced stage GOM, but also early stage GOM. Mutant mice did not develop the most severe GOM stage seen in patient material. This absence of end-stage GOM in mice was associated with an overall lack of histological vascular pathology, which may explain why the mice did not reveal functional deficits in cerebral blood flow, cognition and motor function. Taken together, our data indicate that GOM progress over time, and that new GOM deposits are continuously being formed. The GOM staging system we introduce here allows for uniform GOM deposit classification in future mouse and human studies, which may lead to more insight into a potential association between GOM stage and CADASIL disease severity, and the role of GOM in disease progression.

Functional variation at an expressed MHC class IIβ locus associates with Ranavirus infection intensity in larval anuran populations - Anna E. Savage; Carly R. Muletz-Wolz; Evan H. Campbell Grant; Robert C. Fleischer; Kevin P. Mulder (Immunogenetics, 2019)

Methyl Jasmonate Changes the Composition and Distribution Rather than the Concentration of Defence Compounds: a Study on Pyrrolizidine Alkaloids - Xianqin Wei; Klaas Vrieling; Patrick P. J. Mulder; Peter G. L. Klinkhamer (Journal of Chemical Ecology, 2019)

Lost but not forgotten: MHC genotypes predict overwinter survival despite depauperate MHC diversity in a declining frog - Anna E. Savage; Kevin P. Mulder; Taina Torres; Stuart Wells (Conservation Genetics, 2018)

The use of an electronic clinical rule to discontinue chronically used benzodiazepines and related Z drugs - C. Mestres Gonzalvo; V. Milosevic; B. P. C. van Oijen; H. A. J. M. de Wit; K. P. G. M. Hurkens; W. J. Mulder; R. Janknegt; J. M. G. A. Schols; F. R. Verhey; B. Winkens; P. H. M. van der Kuy (European Journal of Clinical Pharmacology, 2018)

Fate of pyrrolizidine alkaloids during processing of milk of cows treated with ragwort - Monique de Nijs; Patrick P. J. Mulder; Mirjam D. Klijnstra; Frank Driehuis; Ron L. A. P. Hoogenboom (Food Additives & Contaminants: Part A, 2017)

Increased variance in temperature and lag effects alter phenological responses to rapid warming in a subarctic plant community - Christa P. H. Mulder; David T. Iles; Robert F. Rockwell (Global Change Biology, 2017)
Summer temperature on the Cape Churchill Peninsula (Manitoba, Canada) has increased rapidly over the past 75 years, and flowering phenology of the plant community is advanced in years with warmer temperatures (higher cumulative growing degree days). Despite this, there has been no overall shift in flowering phenology over this period. However, climate change has also resulted in increased interannual variation in temperature; if relationships between phenology and temperature are not linear, an increase in temperature variance may interact with an increase in the mean to alter how community phenology changes over time. In our system, the relationship between phenology and temperature was log‐linear, resulting in a steeper slope at the cold end of the temperature spectrum than at the warm end. Because below‐average temperatures had a greater impact on phenology than above‐average temperatures, the long‐term advance in phenology was reduced. In addition, flowering phenology in a given year was delayed if summer temperatures were high the previous year or 2 years earlier (lag effects), further reducing the expected advance over time. Phenology of early‐flowering plants was negatively affected only by temperatures in the previous year, and that of late‐flowering plants primarily by temperatures 2 years earlier. Subarctic plants develop leaf primordia one or more years prior to flowering (preformation); these results suggest that temperature affects the development of flower primordia during this preformation period. Together, increased variance in temperature and lag effects interacted with a changing mean to reduce the expected phenological advance by 94%, a magnitude large enough to account for our inability to detect a significant advance over time. We conclude that changes in temperature variability and lag effects can alter trends in plant responses to a warming climate and that predictions for changes in plant phenology under future warming scenarios should incorporate such effects.

Transfer of pyrrolizidine alkaloids from various herbs to eggs and meat in laying hens - Patrick P. J. Mulder; Susannah L. de Witte; Geert M. Stoopen; Jan van der Meulen; Piet G. van Wikselaar; Erik Gruys; Maria J. Groot; Ron L. A. P. Hoogenboom (Food Additives & Contaminants: Part A, 2016)

Adaptive and neutral genetic differentiation among Scottish and endangered Irish red grouse (Lagopus lagopus scotica) - Yvonne Meyer-Lucht; Kevin P. Mulder; Marianne C. James; Barry J. McMahon; Kieran Buckley; Stuart B. Piertney; Jacob Höglund (Conservation Genetics, 2016)

Effects of non-native Melilotus albus on pollination and reproduction in two boreal shrubs - Katie V. Spellman; Laura C. Schneller; Christa P. H. Mulder; Matthew L. Carlson (Oecologia, 2015)

Explant cultures of atopic dermatitis biopsies maintain their epidermal characteristics in vitro - Vincent van Drongelen; Mogbekeloluwa O. Danso; Jacoba J. Out; Aat Mulder; Adriana P. M. Lavrijsen; Joke A. Bouwstra; Abdoelwaheb El Ghalbzouri (Cell and Tissue Research, 2015)

Air and seawater pollution and air–sea gas exchange of persistent toxic substances in the Aegean Sea: spatial trends of PAHs, PCBs, OCPs and PBDEs - Gerhard Lammel; Ondřej Audy; Athanasios Besis; Christos Efstathiou; Kostas Eleftheriadis; Jiři Kohoutek; Petr Kukučka; Marie D. Mulder; Petra Přibylová; Roman Prokeš; Tatsiana P. Rusina; Constantini Samara; et al. (Environmental Science and Pollution Research, 2015)

Adaptation strategies to maintain dunes as flexible coastal flood defense in The Netherlands - Joep G. S. Keijsers; Alessio Giardino; Ate Poortinga; Jan P. M. Mulder; Michel J. P. M. Riksen; Giorgio Santinelli (Mitigation and Adaptation Strategies for Global Change, 2015)

Musculoskeletal effects of 5 days of bed rest with and without locomotion replacement training - E. Mulder; G. Clément; D. Linnarsson; W. H. Paloski; F. P. Wuyts; J. Zange; P. Frings-Meuthen; B. Johannes; V. Shushakov; M. Grunewald; N. Maassen; J. Buehlmeier; et al. (European Journal of Applied Physiology, 2015)

Nitrogen-depleted Chlorella zofingiensis produces astaxanthin, ketolutein and their fatty acid esters: a carotenoid metabolism study - Kim J. M. Mulders; Yannick Weesepoel; Pierre Bodenes; Packo P. Lamers; Jean-Paul Vincken; Dirk E. Martens; Harry Gruppen; René H. Wijffels (Journal of Applied Phycology, 2015)

Long-term transmission of measles virus in Central and continental Western Europe - S. Santibanez; J. M. Hübschen; C. P. Muller; F. Freymuth; M. M. Mosquera; M. Ben Mamou; M. N. Mulders; K. E. Brown; R. Myers; A. Mankertz (Virus Genes, 2015)

Testing the Generalist-Specialist Dilemma: The Role of Pyrrolizidine Alkaloids in Resistance to Invertebrate Herbivores in Jacobaea Species - Xianqin Wei; Klaas Vrieling; Patrick P. J. Mulder; Peter G. L. Klinkhamer (Journal of Chemical Ecology, 2015)

Disentangling above‐ and belowground neighbor effects on the growth, chemistry, and arthropod community on a focal plant - Martine Kos; Tibor Bukovinszky; Patrick P. J. Mulder; T. Martijn Bezemer (Ecology, 2015)
Neighboring plants can influence arthropods on a focal plant, and this can result in associational resistance or associational susceptibility. These effects can be mediated by above‐ and belowground interactions between the neighbor and focal plant, but determining the relative contribution of the above‐ and belowground effects remains an open challenge. We performed a common garden experiment with a design that enabled us to disentangle the above‐ and belowground effects of five different plant species on the growth and chemistry of the focal plant ragwort ( Jacobaea vulgaris ), and the arthropod community associated with this plant. Aboveground effects of different neighboring plant species were more important for the growth and quality of J. vulgaris and for the arthropod abundance on this plant than belowground effects of neighbors. This remained true when only indirect neighbor effects (via affecting the biomass or quality of the focal plant) were considered. The aboveground neighbor effects on arthropod abundance on the focal plant were strongly negative. However, the magnitude of the effect depended on the identity of the neighboring species, and herbivore abundance on the focal plant was higher when surrounded by conspecific than when surrounded by heterospecific plants. We also observed interactions between above‐ and belowground neighbor effects, indicating that these effects may be nonadditive. We conclude that above‐ and belowground associational effects are not equally strong, and that neighbor effects on plant–arthropod interactions occur predominantly aboveground.

Seabirds as agents of spatial heterogeneity on New Zealand’s offshore islands - Melody S. Durrett; David A. Wardle; Christa P. H. Mulder; Ronald P. Barry (Plant and Soil, 2014)

OsJAR1 is required for JA-regulated floret opening and anther dehiscence in rice - Yuguo Xiao; Yi Chen; Tatsiana Charnikhova; Patrick P. J. Mulder; Jeroen Heijmans; Angela Hoogenboom; Adamantia Agalou; Corinne Michel; Jean-Benoit Morel; Ludovico Dreni; Martin M. Kater; Harro Bouwmeester; et al. (Plant Molecular Biology, 2014)

Susceptibility of burned black spruce (Picea mariana) forests to non-native plant invasions in interior Alaska - Katie V. Spellman; Christa P. H. Mulder; Teresa N. Hollingsworth (Biological Invasions, 2014)

Intra- and inter-laboratory validation of a dipstick immunoassay for the detection of tropane alkaloids hyoscyamine and scopolamine in animal feed - Patrick P.J. Mulder; Christoph von Holst; Noan Nivarlet; Hans P. van Egmond (Food Additives & Contaminants: Part A, 2014)

Growth and pigment accumulation in nutrient-depleted Isochrysis aff. galbana T-ISO - Kim J. M. Mulders; Yannick Weesepoel; Packo P. Lamers; Jean-Paul Vincken; Dirk E. Martens; René H. Wijffels (Journal of Applied Phycology, 2013)

Increased paternal age and the influence on burden of genomic copy number variation in the general population - Jacobine E. Buizer-Voskamp; Hylke M. Blauw; Marco P. M. Boks; Kristel R. van Eijk; Jan H. Veldink; Eric A. M. Hennekam; Jacob A. S. Vorstman; Flip Mulder; Henning Tiemeier; André G. Uitterlinden; Lambertus A. Kiemeney; Leonard H. van den Berg; et al. (Human Genetics, 2013)

Pyrrolizidine Alkaloid Composition Influences Cinnabar Moth Oviposition Preferences in Jacobaea Hybrids - Dandan Cheng; Eddy van der Meijden; Patrick P. J. Mulder; Klaas Vrieling; Peter G. L. Klinkhamer (Journal of Chemical Ecology, 2013)

Effects of Root Herbivory on Pyrrolizidine Alkaloid Content and Aboveground Plant-Herbivore-Parasitoid Interactions in Jacobaea Vulgaris - Olga Kostenko; Patrick P. J. Mulder; T. Martijn Bezemer (Journal of Chemical Ecology, 2013)

Climate change, phenology, and habitat degradation: drivers of gosling body condition and juvenile survival in lesser snow geese - Lise M. Aubry; Robert F. Rockwell; Evan G. Cooch; Rodney W. Brook; Christa P. H. Mulder; David N. Koons (Global Change Biology, 2013)
Nesting migratory geese are among the dominant herbivores in (sub) arctic environments, which have undergone unprecedented increases in temperatures and plant growing days over the last three decades. Within these regions, the H udson B ay L owlands are home to an overabundant breeding population of lesser snow geese that has dramatically damaged the ecosystem, with cascading effects at multiple trophic levels. In some areas the overabundance of geese has led to a drastic reduction in available forage. In addition, warming of this region has widened the gap between goose migration timing and plant green‐up, and this ‘mismatch’ between goose and plant phenologies could in turn affect gosling development. The dual effects of climate change and habitat quality on gosling body condition and juvenile survival are not known, but are critical for predicting population growth and related degradation of (sub) arctic ecosystems. To address these issues, we used information on female goslings marked and measured between 1978 and 2005 (4125 individuals). Goslings that developed within and near the traditional center of the breeding colony experienced the effects of long‐term habitat degradation: body condition and juvenile survival declined over time. In newly colonized areas, however, we observed the opposite pattern (increase in body condition and juvenile survival). In addition, warmer than average winters and summers resulted in lower gosling body condition and first‐year survival. Too few plant ‘growing days’ in the spring relative to hatch led to similar results. Our assessment indicates that geese are recovering from habitat degradation by moving to newly colonized locales. However, a warmer climate could negatively affect snow goose populations in the long‐run, but it will depend on which seasons warm the fastest. These antagonistic mechanisms will require further study to help predict snow goose population dynamics and manage the trophic cascade they induce.

Legacy effects of aboveground–belowground interactions - Olga Kostenko; Tess F. J. van de Voorde; Patrick P. J. Mulder; Wim H. van der Putten; T. Martijn Bezemer (Ecology Letters, 2012)
Root herbivory can greatly affect the performance of aboveground insects via changes in plant chemistry. These interactions have been studied extensively in experiments where aboveground and belowground insects were feeding on the same plant. However, little is known about how aboveground and belowground organisms interact when they feed on plant individuals that grow after each other in the same soil. We show that feeding by aboveground and belowground insect herbivores on ragwort ( Jacobaea vulgaris ) plants exert unique soil legacy effects, via herbivore‐induced changes in the composition of soil fungi. These changes in the soil biota induced by aboveground and belowground herbivores of preceding plants greatly influenced the pyrrolizidine alkaloid content, biomass and aboveground multitrophic interactions of succeeding plants. We conclude that plant‐mediated interactions between aboveground and belowground insects are also important when they do not feed simultaneously on the same plant.

Low attack rate of novel influenza A (H1N1) virus infection among healthcare workers: a prospective study in a setting with an elaborated containment plan - Patrick M. Smit; Jan W. Mulder; Mohamed Ahdi; Ron Gerritsen; Stanley Darma; Paul H. M. Smits; Chris Roggeveen; Eric C. M. van Gorp; Guus F. Rimmelzwaan; Dees P. M. Brandjes (International Archives of Occupational and Environmental Health, 2012)

Putative role of the adenosine A3 receptor in the antiproliferative action of N 6-(2-isopentenyl)adenosine - Clara C. Blad; Jacobien K. von Frijtag Drabbe Künzel; Henk de Vries; Thea Mulder-Krieger; Sara Bar-Yehuda; Pnina Fishman; Adriaan P. IJzerman (Purinergic Signalling, 2011)

Patient-Specific Modeling of Cerebral Blood Flow: Geometrical Variations in a 1D Model - G. Mulder; A. Marzo; A. C. B. Bogaerds; S. C. Coley; P. Rongen; D. R. Hose; F. N. van de Vosse (Cardiovascular Engineering and Technology, 2011)

Screening of plant toxins in food, feed and botanicals using full-scan high-resolution (Orbitrap) mass spectrometry - H.G.J. Mol; R.C.J. Van Dam; P. Zomer; P.P.J. Mulder (Food Additives & Contaminants: Part A, 2011)

The Relationship between Structurally Different Pyrrolizidine Alkaloids and Western Flower Thrips Resistance in F2 Hybrids of Jacobaea vulgaris and Jacobaea aquatica - Dandan Cheng; Heather Kirk; Klaas Vrieling; Patrick P. J. Mulder; Peter G. L. Klinkhamer (Journal of Chemical Ecology, 2011)

East–west genetic differentiation in Musk Ducks (Biziura lobata) of Australia suggests late Pleistocene divergence at the Nullarbor Plain - P.-J. Guay; R. T. Chesser; R. A. Mulder; A. D. Afton; D. C. Paton; K. G. McCracken (Conservation Genetics, 2010)

General stabilizing effects of plant diversity on grassland productivity through population asynchrony and overyielding - A. Hector; Y. Hautier; P. Saner; L. Wacker; R. Bagchi; J. Joshi; M. Scherer-Lorenzen; E. M. Spehn; E. Bazeley-White; M. Weilenmann; M. C. Caldeira; P. G. Dimitrakopoulos; et al. (Ecology, 2010)
Insurance effects of biodiversity can stabilize the functioning of multispecies ecosystems against environmental variability when differential species' responses lead to asynchronous population dynamics. When responses are not perfectly positively correlated, declines in some populations are compensated by increases in others, smoothing variability in ecosystem productivity. This variance reduction effect of biodiversity is analogous to the risk‐spreading benefits of diverse investment portfolios in financial markets. We use data from the BIODEPTH network of grassland biodiversity experiments to perform a general test for stabilizing effects of plant diversity on the temporal variability of individual species, functional groups, and aggregate communities. We tested three potential mechanisms: reduction of temporal variability through population asynchrony; enhancement of long‐term average performance through positive selection effects; and increases in the temporal mean due to overyielding. Our results support a stabilizing effect of diversity on the temporal variability of grassland aboveground annual net primary production through two mechanisms. Two‐species communities with greater population asynchrony were more stable in their average production over time due to compensatory fluctuations. Overyielding also stabilized productivity by increasing levels of average biomass production relative to temporal variability. However, there was no evidence for a performance‐enhancing effect on the temporal mean through positive selection effects. In combination with previous work, our results suggest that stabilizing effects of diversity on community productivity through population asynchrony and overyielding appear to be general in grassland ecosystems.

The weight of representing the body: addressing the potentially indefinite number of body representations in healthy individuals - Marjolein P. M. Kammers; Joris Mulder; Frédérique de Vignemont; H. Chris Dijkerman (Experimental Brain Research, 2010)

Invasive rats alter woody seedling composition on seabird-dominated islands in New Zealand - Madeline N. Grant-Hoffman; Christa P. Mulder; Peter J. Bellingham (Oecologia, 2010)

Effects of invasive rats and burrowing seabirds on seeds and seedlings on New Zealand islands - Madeline N. Grant-Hoffman; Christa P. H. Mulder; Peter J. Bellingham (Oecologia, 2010)

Soil-borne microorganisms and soil-type affect pyrrolizidine alkaloids in Jacobaea vulgaris - Lotte Joosten; Patrick P. J. Mulder; Peter G. L. Klinkhamer; Johannes A. van Veen (Plant and Soil, 2009)

Biotechnology, environmental forcing, and unintended trophic cascades - Christian Mulder; Lambertus A. P. Lotz (Arthropod-Plant Interactions, 2009)

Species removal and experimental warming in a subarctic tundra plant community - Christian Rixen; Christa P. H. Mulder (Oecologia, 2009)

Direct and indirect effects of rats: does rat eradication restore ecosystem functioning of New Zealand seabird islands? - Christa P. H. Mulder; M. Nicole Grant-Hoffman; David R. Towns; Peter J. Bellingham; David A. Wardle; Melody S. Durrett; Tadashi Fukami; Karen I. Bonner (Biological Invasions, 2009)

Indirect effects of invasive predators on litter decomposition and nutrient resorption on seabird‐dominated islands - David A. Wardle; Peter J. Bellingham; Karen I. Bonner; Christa P. H. Mulder (Ecology, 2009)
Despite recent interest in the ecosystem impacts of invasive aboveground organisms, most work in this area has focused on effects of invasive plants, and the effects of invasive herbivores and predators remain poorly understood. We studied 18 forested, offshore islands in northern New Zealand. Nine of these host high densities of burrowing seabirds that serve as ecosystem drivers by transporting nutrients from the ocean to land. The other nine have been invaded over the past 50–150 years by rat species introduced from Europe which serve as predators of seabird eggs and chicks and severely reduce their densities. We collected fully expanded leaves and fresh leaf litter from invaded and uninvaded islands for each of 12 perennial plant species that represent a wide spectrum of life forms from ground dwelling to emergent canopy species. We found that, across these species, invasion by rats significantly reduced nitrogen (N) but not phosphorus (P) concentrations of foliage and litter, promoted N but not P resorption from leaves before litter fall, and reduced the release of N but not P from decomposing litter. Rat invasion also negatively affected litter decomposability but had no overall effects on litter quality variables other than N. Our results provide evidence that rat invasion causes more conservative cycling of N but not P through foliage and litter and limitation of ecological processes by N but not P. We found few instances in which the effects of rat invasion on response variables varied significantly across plant species, meaning that invasion had similar effects for species that varied greatly in growth form and foliar and litter quality. Further, correlation analyses across the 12 species showed that foliar and litter quality traits were poor predictors of how invasion effects on resorption and decomposition variables varied among species. Our results show that the effects of invasive predators on native prey can have substantial indirect effects on variables relevant for ecosystem functioning. These types of effects are probably widespread, especially given the role of seabirds in improving soil fertility in many coastal ecosystems worldwide and the wide global distribution of predators of seabirds.

Should medical students learn to develop a personal formulary? - T. P. G. M. De Vries; J. M. A. Daniels; C. W. Mulder; O. A. Groot; L. Wewerinke; K. I. Barnes; H. A. Bakathir; N. A. G. M. Hassan; L. Van Bortel; M. Kriska; B. Santoso; E. J. Sanz; et al. (European Journal of Clinical Pharmacology, 2008)

Lessons learnt from a participatory integrated assessment of greenhouse gas emission reduction options in firms - Serge I. P. Stalpers; André R. van Amstel; Rob B. Dellink; Ivo Mulder; Saskia E. Werners; Carolien Kroeze (Mitigation and Adaptation Strategies for Global Change, 2008)

Tuning the tide: creating ecological conditions for tidal marsh development in a flood control area - T. Maris; T. Cox; S. Temmerman; P. De Vleeschauwer; S. Van Damme; T. De Mulder; E. Van den Bergh; P. Meire (Hydrobiologia, 2007)

Regional Sediment Deficits in the Dutch Lowlands: Implications for Long-Term Land-Use Options (8 pp) - Michiel J. van der Meulen; Ad J. F. van der Spek; Ger de Lange; Stephan H. L. L. Gruijters; Serge F. van Gessel; Buu-Long Nguyen; Denise Maljers; Jeroen Schokker; Jan P. M. Mulder; Rob A. A. van der Krogt (Journal of Soils and Sediments, 2007)

Above‐ and below‐ground impacts of introduced predators in seabird‐dominated island ecosystems - Tadashi Fukami; David A. Wardle; Peter J. Bellingham; Christa P. H. Mulder; David R. Towns; Gregor W. Yeates; Karen I. Bonner; Melody S. Durrett; Madeline N. Grant‐Hoffman; Wendy M. Williamson (Ecology Letters, 2006)
Predators often exert multi‐trophic cascading effects in terrestrial ecosystems. However, how such predation may indirectly impact interactions between above‐ and below‐ground biota is poorly understood, despite the functional importance of these interactions. Comparison of rat‐free and rat‐invaded offshore islands in New Zealand revealed that predation of seabirds by introduced rats reduced forest soil fertility by disrupting sea‐to‐land nutrient transport by seabirds, and that fertility reduction in turn led to wide‐ranging cascading effects on belowground organisms and the ecosystem processes they drive. Our data further suggest that some effects on the belowground food web were attributable to changes in aboveground plant nutrients and biomass, which were themselves related to reduced soil disturbance and fertility on invaded islands. These results demonstrate that, by disrupting across‐ecosystem nutrient subsidies, predators can indirectly induce strong shifts in both above‐ and below‐ground biota via multiple pathways, and in doing so, act as major ecosystem drivers.

Past and present sedimentary activity in the Capbreton Canyon, southern Bay of Biscay - M. Gaudin; T. Mulder; P. Cirac; S. Berné; P. Imbert (Geo-Marine Letters, 2006)

Advanced snowmelt causes shift towards positive neighbour interactions in a subarctic tundra community - SONJA WIPF; CHRISTIAN RIXEN; CHRISTA P. H. MULDER (Global Change Biology, 2006)
Positive and negative species interactions are important factors in structuring vegetation communities. Studies in many ecosystems have focussed on competition; however, facilitation has often been found to outweigh competition under harsh environmental conditions. The balance between positive and negative species interactions is known to shift along spatial, temporal and environmental gradients and thus is likely to be affected by climate change. Winter temperature and precipitation patterns in Interior Alaska are rapidly changing and could lead to warmer winters with a shallow, early melting snow cover in the near future. We conducted snow manipulation and neighbour removal experiments to test whether the relative importance of positive and negative species interactions differs between three winter climate scenarios in a subarctic tundra community. In plots with ambient, manually advanced or delayed snowmelt, we assessed the relative importance of neighbours for survival, phenology, growth and reproduction of two dwarf shrub species. Under ambient conditions and after delayed snowmelt, positive and negative neighbour effects were generally balanced, but when snowmelt was advanced we found overall facilitative neighbour effects on survival, phenology, growth and reproduction of Empetrum nigrum , the earlier developing of the two target species. As earlier snowmelt was correlated with colder spring temperatures and a higher number of frosts, we conclude that plants experienced harsher environmental conditions after early snowmelt and that neighbours could have played an important role in ameliorating the physical environment at the beginning of the growing season.

The western part of the Gulf of Cadiz: contour currents and turbidity currents interactions - T. Mulder; P. Lecroart; V. Hanquiez; E. Marches; E. Gonthier; J.-C. Guedes; E. Thiébot; B. Jaaidi; N. Kenyon; M. Voisset; C. Perez; M. Sayago; et al. (Geo-Marine Letters, 2006)

Mating system, philopatry and patterns of kinship in the cooperatively breeding subdesert mesite Monias benschi - N. SEDDON; W. AMOS; G. ADCOCK; P. JOHNSON; K. KRAAIJEVELD; F. J. L. KRAAIJEVELD‐SMIT; W. LEE; G. D. SENAPATHI; R. A. MULDER; J. A. TOBIAS (Molecular Ecology, 2005)
In the first molecular study of a member of the threatened avian family, Mesitornithidae, we used nine polymorphic microsatellite loci to elucidate parentage, patterns of within‐group kinship and occurrence of extra‐group paternity in the subdesert mesite Monias benschi , of southwest Madagascar. We found this cooperatively breeding species to have a very fluid mating system. There was evidence of genetic monogamy and polygynandry: of the nine groups with multiple offspring, six contained one breeding pair with unrelated helpers and three contained multiple male and female breeders with related helpers. Although patterns of within‐group kinship varied, there was a strong positive relationship between group size and relatedness, suggesting that groups form by natal philopatry. There was also a strong positive correlation between within‐sex and between‐sex relatedness, indicating that unlike most cooperatively breeding birds, philopatry involved both sexes. In contrast to predictions of kin selection and reproductive skew models, all monogamous groups contained unrelated individuals, while two of the three polygynandrous groups were families. Moreover, although between‐group variation in seasonal reproductive success was related to within‐group female relatedness, relatedness among males and between the sexes had no bearing on a group's reproductive output. While kin selection may underlie helping behaviour in females, factors such as direct long‐term fitness benefits of group living probably determine helping in males. Of the 14 offspring produced by fully sampled groups, at least two were sired by males from neighbouring groups: one by a breeding male and one by a nonbreeding male, suggesting that males may augment their reproductive success through extra‐group paternity.

Numerical abundance and biodiversity of below‐ground taxocenes along a pH gradient across the Netherlands - Christian Mulder; Harm J. Van Wijnen; Annemarie P. Van Wezel (Journal of Biogeography, 2005)
Aim Taxocenes are regulated by different kinds of predictors, but can broad‐scale patterns of prokaryotes (bacteria) and eukaryotes (such as fungi and invertebrates) be ascribed to soil acidity? We sought to test for relationships between the numerical abundances of bacteria, microfungi, nematodes and arthropods along a pH gradient. Location 284 agro‐ecosystems on Pleistocene sand across the Netherlands. Methods Generalized Linear Models (GLM) and stepwise regressions were applied, using soil‐ and leaf‐litter organisms sampled from a land‐cover network. Results The major variation in the numerical abundance of the organisms belonging to the investigated taxocenes could be ascribed to soil acidity. Contrary to expectations, the effects of temperature on numerical abundance were significant only for Fungi and Nematoda ( P P F ‐value = 22.45, P Main conclusions There were strong relationships between the numerical abundances of all the investigated taxocenes and the field‐measured soil acidity ( P

Effect of Straw Application on Rice Yields and Nutrient Availability on an Alkaline and a pH-neutral Soil in a Sahelian Irrigation Scheme - P. J. A. van Asten; P. M. van Bodegom; L. M. Mulder; M. J. Kropff (Nutrient Cycling in Agroecosystems, 2005)

Identification of Stabilized Dynorphin Derivatives for Suppressing Tolerance in Morphine-Dependent Rats - Suliman I. Al-Fayoumi; Boglarka Brugos; Vikram Arya; Esther Mulder; Barbel Eppler; Andre P. Mauderli; Günther Hochhaus (Pharmaceutical Research, 2004)

Extra‐pair paternity does not result in differential sexual selection in the mutually ornamented black swan ( Cygnus atratus ) - K. Kraaijeveld; P. J. Carew; T. Billing; Greg J. Adcock; Raoul A. Mulder (Molecular Ecology, 2004)
We studied patterns of parentage in 85 broods (332 cygnets) of black swans during three breeding seasons, using a set of eight polymorphic microsatellite markers. We detected both intraspecific brood parasitism (IBP;

High sequence diversity in infectious bursal disease virus serotype 1 in poultry and turkey suggests West-African origin of very virulent strains - A. A. Owoade; M. N. Mulders; J. Kohnen; W. Ammerlaan; C. P. Muller (Archives of Virology, 2004)

Combination of Vascular Endothelial Growth Factor (VEGF) and Thymidine Phosphorylase (TP) to Improve Angiogenic Gene Therapy - Diane Bouïs; Mirjam C. Boelens; Erna Peters; Pieter Koolwijk; Gerrie Stob; Ido P. Kema; Marco Klinkenberg; Nanno H. Mulder; Geke A.P. Hospers (Angiogenesis, 2003)

The Gulf of Cadiz: an unstable giant contouritic levee - T. Mulder; M. Voisset; P. Lecroart; E. Le Drezen; E. Gonthier; V. Hanquiez; J.-C. Faugres; E. Habgood; F. J. Hernandez-Molina; F. Estrada; E. Llave-Barranco; D. Poirier; et al. (Geo-Marine Letters, 2003)

Suppressive musculocutaneous reflexes in tibialis anterior following upper leg stimulation at the end of the swing phase - H. W. A. A. Van de Crommert; P. J. M. Steijvers; Th. Mulder; J. Duysens (Experimental Brain Research, 2003)

How plant diversity and legumes affect nitrogen dynamics in experimental grassland communities - C. Mulder; A. Jumpponen; P. Högberg; K. Huss-Danell (Oecologia, 2002)

Pancreatic-Type Ribonuclease 1 Gene Duplications in Rat Species - Jean-Yves F. Dubois; Peter A. Jekel; Patty P.M.F.A. Mulder; Anton P. Bussink; François M. Catzeflis; Antonella Carsana; Jaap J. Beintema (Journal of Molecular Evolution, 2002)

The biology of insularity: an introduction - Donald R. Drake; Christa P. H. Mulder; David R. Towns; Charles H. Daugherty (Journal of Biogeography, 2002)
Insular environments, ranging from oceanic islands to fragments of once‐contiguous natural systems, have long been used by biologists to test basic principles of ecology, evolution and biogeography. More recently, insular environments have figured prominently in conservation ecology, where the aim has usually been to conserve species or assemblages unique to isolated habitats. Improving the level of communication among the evolutionary biologists, theoretical ecologists and conservation biologists who study insular biotas will work to the benefit of all. This volume was inspired by a recent conference on the ecology of insular biotas, in which participants from a wide range of disciplines came together to compare ecological processes across a variety of taxonomic groups inhabiting a wide range of isolated environments. In this introduction, we point out the themes underlying these very diverse contributions. First we elaborate on the value of islands for elucidating processes underlying ecosystem functioning, population dynamics of reintroduced species, and restoration of disturbed habitats, and emphasize those areas where the use of islands could be expanded. The second section focuses on the link between ecology and evolutionary processes in insular systems and includes examples from oceanic islands, naturally patchy habitats and recently fragmented habitats. The third section illustrates some of the ways that invasive alien species on oceanic islands affect plant–animal mutualisms, particularly seed dispersal and pollination. The final section, on consequences of habitat fragmentation, focuses mainly on studies that describe the consequences that fragmentation has for plants and animals as they are forced into artificially insular environments. We close with a study that points out the differences among types of insular systems and identifies gaps in our knowledge of insular biotas, particularly the importance of explicitly incorporating patch type, age and patch–matrix contrasts in research. Finally, we recommend a greater emphasis on linking ecological theory and applied research, and improving communication between those who ask basic ecological questions and those who use insular systems for conservation.

Local adaptation enhances performance of common plant species - J. Joshi; B. Schmid; M. C. Caldeira; P. G. Dimitrakopoulos; J. Good; R. Harris; A. Hector; K. Huss‐Danell; A. Jumpponen; A. Minns; C. P. H. Mulder; J. S. Pereira; et al. (Ecology Letters, 2001)
Geographic variation can lead to the evolution of different local varieties, even in widespread forage plants. We investigated the performance of common forage plants in relation to their genetic diversity and local adaptation at a continental scale using reciprocal transplants at eight field sites across Europe over a 2‐year period. The overall performance of the three test species, Trifolium pratense , Dactylis glomerata , Plantago lanceolata , was generally highest for plants replanted at their home site and declined with increasing transplanting distance. The three species differed in the fitness components responsible for the increased overall performance and selection advantage at home sites. In addition to the effects of local adaptation, the majority of measured traits in all three species also showed ecotypic variation. However, no single ecotype of any species was able to outperform the locally adapted strains and do best at all sites, highlighting the importance of maintaining these plant genetic resources.

A few months-old storm-generated turbidite deposited in the Capbreton Canyon (Bay of Biscay, SW France) - Mulder T.; Weber O.; Anschutz P.; Jorissen F.; Jouanneau J.-M. (Geo-Marine Letters, 2001)

Burrowing seabirds and reptiles: impacts on seeds, seedlings and soils in an island forest in New Zealand - Christa P. Mulder; Susan N. Keall (Oecologia, 2001)

Induction of Marine Mollusc Stress Proteins by Chemical or Physical Stress - M. J. Snyder, E. Girvetz, E. P. Mulder (Archives of Environmental Contamination and Toxicology, 2001)

Bremazocine reduces unrestricted free-choice ethanol self-administration in rats without affecting sucrose preference - P. Nestby; A. N. M. Schoffelmeer; J. R. Homberg; G. Wardeh; T. J. De Vries; A. H. Mulder; L. J. M. J. Vanderschuren (Psychopharmacology, 1999)

Preliminary selection of antagonists ofErwinia carotovora subsp.atroseptica (Van Hall) Dye for application during green crop lifting of seed potato tubers - P. Kastelein; E. G. Schepel; A. Mulder; L. J. Turkensteen; J. W. L. Van Vuurde (Potato Research, 1999)

Abstracts of Papers presented at a Workshop on Ecology of Botrytis and Sclerotinia and their Interaction With Other Microorganisms Abstracts of Papers Presented at a Workshop on Genetic Aspects ofFusarium oxysporum and Related Species Abstracts of Papers and Discussion Contributions Presented at the Dutch-Israeli (Diarp) Workshop on Environment-Friendly Crop Protection of the Flower Industry to Suit Future Market Trends - A. Ten Have; W. Oude Breuil; J. Wubben; W. Mulder; J. Visser; J. van Kan; T. Quidde; P. Tudzynski; T. M. O’Neill; G. De Meyer; K. Audenaert; J. Bigirimana; et al. (Phytoparasitica, 1999)

Unrestricted free-choice ethanol self-administration in rats causes long-term neuroadaptations in the nucleus accumbens and caudate putamen - P. Nestby; L. J. M. J. Vanderschuren; T. J. De Vries; A. H. Mulder; G. Wardeh; F. Hogenboom; A. N. M. Schoffelmeer (Psychopharmacology, 1999)

The exchange of functional domains among aquaporins with different transport characteristics - Sabine M. Mulders; Annemiete J. van der Kemp; Sylvie A. Terlouw; Hanneke A. F. van Boxtel; Carel H. van Os; P. M. T. Deen (Pflügers Archiv - European Journal of Physiology, 1998)

Gene therapy for glioblestome multiforme: in vivo tumor transduction with the herpes simplex thymidine kinase gene followed by ganciclovir - G. Stockhammer; J. Brotchi; R. Leblanc; M. Bernstein; G. Schackert; F. Weber; C. Ostertag; N. H. Mulder; H. Mellstedt; R. Seiler; Y. Yonekawa; K. Twerdy; et al. (Journal of Molecular Medicine, 1997)

Magnesium pyridoxal-5′-phosphate glutamate, "A vitamin B 6 derivative", does not affect lipoprotein levels in patients with familial hypercholesterolaemia - H. C. Knipscheer; I. Kindt; A. van den Ende; M. T. Nurmohamed; H. Smalbraak; W. J. Mulder; J. J. P. Kastelein (European Journal of Clinical Pharmacology, 1997)

Polychlorinated biphenyls, dibenzo-p-dioxins, and dibenzofurans in harbor porpoises (Phocoena phocoena) stranded on the Dutch coast between 1990 and 1993 - W. B. van Scheppingen; A. J. I. M. Verhoeven; P. Mulder; M. J. Addink; C. Smeenk (Archives of Environmental Contamination and Toxicology, 1996)

Polychlorinated Biphenyls, Dibenzo- p- dioxins, and Dibenzofurans in Harbor Porpoises ( Phocoena phocoena ) Stranded on the Dutch Coast Between 1990 and 1993 - W. B. van Scheppingen; A. J. I. M. Verhoeven; P. Mulder (Archives of Environmental Contamination and Toxicology, 1996)

A cohesive sediment balance for the Scheldt estuary - D. C. Maldegem; H. P. J. Mulder; A. Langerak (Aquatic Ecology, 1993)

Mutagenicity and cytotoxicity of two regioisomeric mercapturic acids and cysteine S-conjugates of trichloroethylene - Jan N. M. Commandeur; Peter J. Boogaard; Gerard J. Mulder; Nico P. E. Vermeulen (Archives of Toxicology, 1991)

Counterimmunoelectrophoresis compared with complement fixation and passive haemagglutination tests in the evaluation of the immune response in Campylobacter infections - J. R. J. Bnffer; J. C. C. Duifhuis; P. G. H. Mulder (Antonie van Leeuwenhoek, 1987)

Identification and quantitative determination of mercapturic acids formed from Z- and E-1,3-dichloropropene by the rat, using gas chromatography with three different detection techniques - W. Onkenhout; P. P. J. Mulder; P. J. Boogaard; W. Buijs; N. P. E. Vermeulen (Archives of Toxicology, 1986)

Coryneform bacteria of the Arthrobacter type and their reserve material - E. G. Mulder; L. P. T. M. Zevenhuizen (Archives of Microbiology, 1967)

The effect of light on DNA synthesis and related processes in synchronous cultures of Chlorella - F. Wanka; P. F. M. Mulders (Archives of Microbiology, 1967)

Netherlands Society of Microbiology Meeting on February 24, 1962 - K. Kersters; G. J. E. Thijsse; A. F. Schippers-Lammertse; G. J. P. Schaap; J. H. Bekker; M. Van Poucke; J. J. Joubert; E. G. Mulder; W. L. Van Veen; A. Kaars Sijpestein; J. Kaslander; D. A. A. Mossel; et al. (Antonie van Leeuwenhoek, 1962)